(untitled) (Tanzania Medical Journal, 2020)
Background Sickle cell disease is one of group of blood disorders and diseases that affect red blood cells. Like other haemoglobinopathies, sickle cell disease is inherited single-gene disorders inherited as autosomal co-dominant traits characterized by a single point mutation in the ?-chain of human haemoglobin leading to life-long illness. The severity of the disease varies widely from person to person essentially due to resultant multi-organ failure including liver dysfunction, which can be multifactorial. Broad Objective This study, was carried out to determine the association and potential role hepatic enzymes as biochemical indices may have on the severity of sickle cell anaemia diseases. Methods This was cross-sectional study that was done at sickle cell clinic at Muhimbili National Hospital in Dar es Salaam, Tanzania using an English checklist as a main research tool with a sample size of 75 eligible sickle cell patients. All sickle cell patients who had been attending clinic from September 2016 to October 2016 and had hepatic enzymes test being done were included in the study. Categorical variables were compared using Chi-Square (c2) and binary variables tested using Cochran–Mantel–Haenszel test with p-values <0.05 considered statistically significant. The main findings show that, there was significant association between hepatomegally and liver function tests in patients with sickle cell disease. The association between hepatomegaly and abnormalities in all liver function tests, including alanine transaminase (ALT), aspartate transaminase (AST), bilirubin, albumin and total protein levels was statistically significant (p < 0.05). The Cochran–Mantel–Haenszel test (CMH) for binary categorical variables as well as the association between liver function tests abnormalities and hepatomegaly had exact match (p = 0.05). Conclusion This study found association between abnormalities in liver function tests and hepatomegaly in sickle cell patients to advocate regular screening as an urgent remedy to prevent adverse lethal complications in African setting. Key Words: Hepatic Enzymes, Hepatomegaly, Sickle Cell Disease.